Real marketing - Llanes, Violeta A.; Iturralde, Jose Rene;Pura, Jose Jr. M. (Quezon City, Philippines : Katha Publishing Co, Inc., 1996)
Real Marketing is designed as a basic text for an introductory course in marketing in the Philippines. It provides a comprehensive to the technical, theoretical and practical knowledge of marketing necessary for students to understand the crucial role that marketing plays in the long run success of organizations.
Part one. Foundations of Marketing -- Part two. Marketing Mix Decisions.
Includes bibliographical references.
Keywords: MARKETING -- STUDY AND TEACHING